Pengaruh Transparansi, Akuntabilitas, Dan Kepemimpinan Terhadap Pengelolaan Dana Desa Dengan Partisipasi Masyarakat Sebagai Variabel Mediasi - Rizqi, Andadari Wahyuning (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2025)
Lack of accountability in village fund management has an impact on the delay in absorption of village funds in the next stage, causing the budget not to reach the target. The purpose of this study was to analyze the effect of transparency, accountability, and leadership on village fund management with community participation as a mediating variable in Pabelan District, Semarang Regency. The population in this study were all village officials in Pabelan District, Semarang Regency as many as 132. The sample in this study amounted to 77 village officials with purposive sampling technique. The data collection method was a questionnaire. The data analysis method used descriptive statistical analysis, hypothesis testing and Sobel test. The results of the study showed that transparency, accountability, leadership, and community participation had a positive and significant effect on village fund management. Transparency and accountability had a positive and significant effect on community participation; leadership did not affect community participation. Community participation was able to mediate the effect of transparency and accountability on village fund management. Community participation failed to mediate the effect of leadership on village fund management. The researcher suggested that the village government improve its leadership skills in providing motivation and also making the right decisions so that in this case the management of village funds would be better and optimal.